Regional economic resilience in the European Union: A numerical general equilibrium analysis - Filippo Di Pietro; Patrizio Lecca; Simone Salotti (European Commission, Joint Research Centre (JRC), 2020)
Using a spatial general equilibrium model, this paper investigates the resilience of EU regions under three alternative recessionary shocks, each of them activating different economic adjustments and mechanisms. Using a theoretical framework, we measure the vulnerability, resistance, and recoverability of regions and we identify key regional features affecting the ability of regions to withstand to and recover from unexpected external shocks. The analysis reveals that the response of regions varies according to the nature of the external disturbance and to the pre-shock regional characteristics. Finally, it seems that resilience also depends on factors' mobility.
Keywords: C68; R13; R15; 330; computable general equilibrium model; regional economic resilience; economic shocks